ANALYSIS OF THE EFFECT OF LEADERSHIP, COMMUNICATION, AND MOTIVATION ON TURNOVER INTENTION WITH INTERVENING COMMITMENT ORGANIZATION VARIABLES AT PT MEDIANUSA PERMANA, BATAM CITY - Mangara; Chablullah Wibisono; Ngaliman; Muammar Khaddafi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
The purpose of this study was to determine and analyze the effect of leadership, communication, and motivation on turnover intention with intervening commitment to organizational variables at PT Medianusa Permana, Batam City. The method used is a questionnaire and distributed to 100 respondents. Analysis of statistical data using SEM PLS (Structural Equation Modeling Partial Least Square) and using path analysis to examine the pattern of the relationship between the influence of the dependent variable on the independent, both direct and indirect effects with SMART PLS 3.0 software. The results in the study indicate that leadership has a positive and significant effect on organizational commitment with a p-value of 0.000 <0.05, communication has a positive and significant effect on organizational commitment with a p-value of 0.000 <0.05,turnover intentionwithp-value of 0.771,leadership has a positive and significant effect onturnover intentionwithp-value of 0.008, communicationleadership has a positive and significant effect onturnover intentionwithp-value of 0.004, motivationalhas a positive and significant effect onturnover intentionwithp-value of 0.018,organizational commitment mediates the effect of leadership andturnover intentionwith a p-value of 0.080 < 0.05. organizational commitment mediates the effect of communication andturnover intentionwith a p-value of 0.080 <0.05, and organizational commitment mediates the effect of motivation andturnover intentionwith a p-value of 0.080 < 0.05.